Marketing Public Relations Kecipir.com dalam Membangun Brand Image Social Enterprise - Annisa Alfannafiisah; Lilik Sumarni (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This research is motivated by the increasing public awareness of healthy lifestyles and organic food consumption, which has triggered the emergence of various agritech platforms. Kecipir.com exists as a social enterprise that focuses not only on profit but also on social and environmental missions. This study aims to analyze the implementation of Marketing Public Relations (MPR) by Kecipir.com in building its brand image. The research method used is descriptive qualitative, with data collection techniques including in-depth interviews with the CEO and Social Marketing team of Kecipir.com, as well as social media observations. The results show that Kecipir.com implements MPR strategies through six dimensions: educational publications regarding vegetable benefits, organizing exhibition events, creating news content (blogs), active leadership roles as speakers, public service activities (donations), and consistent identity media. The main findings indicate that health education content is the most effective instrument in shaping Kecipir.com's image as a trusted and socially impactful shopping platform.